3D Electrochemical-Mechanical Battery Simulation Tool: Implementation with Full Cell Simulations and Verification with Operando X-ray Tomography. Issue 2 (1st February 2023) - Wenzler, Nils; Rief, Sebastian; Linden, Sven; Biebl, Fabian; Rütsche, Samuel; Glatt, Ilona; Streit, Anja; Zahn, Raphael; Fingerle, Mathias; Wood, Vanessa
Abstract : Most commercially used electrode materials contract and expand upon cycling. This change in volume influences the microstructure of the cell stack, which in turn impacts a range of performance parameters. Since direct observation of these microstructural changes with operando experiments is challenging and time intensive, a simulation tool that takes a real or artificially generated 3D microstructure and captures the volumetric changes in a cell during cycling would be valuable to enable rapid understanding of the impact of material choice, electrode and cell design, and operating conditions on the microstructural changes and identification of sources of mechanically-driven cell aging. Here, we report the development and verification of such a 3D electrochemical-mechanical tool, and provide an example use-case. We validate the tool by simulating the microstructural evolution of a graphite anode and a Li(Ni, Mn, Co)O2 cathode during cycling and comparing the results to X-ray tomography datasets of these electrodes taken during cycling. As an example use case for such a simulation tool, we explore how different volumetric expansion behaviors of the cathode material impact strain in the cell stack, illustrating how the material selection and its operation impact the mechanical behavior inside a cell.